Lifestyle factors and socioeconomic variables associated with abdominal obesity in Brazilian adolescents - De Moraes, Augusto César Ferreira [UNESP]; Falcão, Mário Cícero (My University, 2013)
Background and aims: Lifestyle variables have a key role in the development of abdominal obesity (AO). The objective of this study was to identify lifestyle factors and socioeconomic variables associated with AO in adolescents. Methods and results: This study carried out a school-based survey in the Brazilian city of Maringá in Paraná. The representative sample was of 991 adolescents (54.5% girls) from both public and private high schools selected through multi-stage random sampling. AO was classified according to waist circumference value. The independent variables studied were: gender, age, socioeconomic level, parental and household characteristics, smoking, alcohol use, physical inactivity, sedentary behaviour and nutrition-related habits. Poisson regression was used with robust variance adjustment to analyse the associations. The analysis was stratified by sexes. The prevalence of AO was 32.7% (girls = 36.3%, boys = 28.4%). In girls, excessive intake of fried foods was inversely associated with AO and excessive consumption of soda was positively associated. In boys, the results demonstrated a negative association with excessive consumption of sweets and soda. Conclusion: It is concluded that the prevalence of AO among adolescents was higher in both sexes. AO is associated with different eating habits in females and males and these relationships are mediated by familial contexts. © Informa UK, Ltd.
Keywords: Adolescents; Cross-sectional study; Low- and middle-income countries; Obesity assessment; Waist circumference; adolescence; alcohol; cross section; habitat type; income; obesity; physical activity; socioeconomic status; survey; abdominal obesity; adolescent; adolescent behavior; age; Brazil; exercise; family size; feeding behavior; female; human; lifestyle; male; nutritional assessment; nutritional status; prevalence; school; sedentary lifestyle; sex difference; smoking; socioeconomics; waist circumference; Adolescent; Adolescent Behavior; Age Factors; Exercise; Family Characteristics; Female; Food Habits; Humans; Life Style; Male; Nutrition Assessment; Nutritional Status; Obesity, Abdominal; Prevalence; Schools; Sedentary Lifestyle; Sex Factors; Smoking; Socioeconomic Factors; Waist Circumference; Maringa; Parana [Brazil]